Epixylic microbial communities as key regulators of methane emissions from submerged wood in a tropical hydroelectric reservoir - Fanny Colas; Léa Cabrol; Jean‐Marc Baudoin; Yves Prairie; Jacques Beauchêne; Vincent Chanudet; Etienne Dambrine; Sophie Guasco; Frederick Jacob; Arthur Szylit; Corinne Valette; Régis Vigouroux; et al. (Limnology and Oceanography, 2026)
Tropical hydroelectric reservoirs are recognized hotspots for greenhouse gas emissions, yet the role of submerged forests in these emissions remains poorly understood. In this study, we investigated the contribution of standing dead trees and their associated epixylic biofilms to methane (CH 4 ) and carbon dioxide (CO 2 ) emissions in the permanently stratified Petit Saut reservoir, French Guiana. We conducted in situ measurements of greenhouse gas fluxes from submerged trunks at multiple depths using static chambers. To unravel the microbial mechanisms underlying CH 4 dynamics, we characterized the active microbial communities and quantified methane production and oxidation rates in both wood and biofilm samples collected above and below the oxycline, using 16S rRNA sequencing and laboratory incubations. Our findings revealed that submerged wood serves as an unrecognized source of in situ CH 4 production, primarily via acetoclastic methanogenesis dominated by Methanosaeta . In contrast, epixylic biofilms acted as effective CH 4 sinks, with methane oxidation largely driven by Methylocystis . Microbial composition and activity showed strong vertical stratification, closely linked to oxygen availability. In situ fluxes mirrored these microbial patterns, with net CH 4 and CO 2 efflux observed below the oxycline and net influx above it. This study highlights the dual role of submerged wood and its surface biofilms in CH 4 cycling, emphasizing the importance of microbial interactions in regulating greenhouse gas emissions from flooded tropical forests. These findings underscore the need to include wood‐mediated processes in greenhouse gas budgets of tropical reservoirs, especially as dam construction continues to expand in forested tropical regions.

Green logistics and circular economy in alleviating CO2 emissions: Does waste generation and GDP growth matter in EU countries? - Mukut Sikder; Chao Wang; Mohammad Mafizur Rahman; Frederick Kwame Yeboah; Andrew Adewale Alola; Jacob Wood (Journal of Cleaner Production, 2024)

Senolytic treatment does not mitigate oxidative stress-induced muscle atrophy but improves muscle force generation in CuZn superoxide dismutase knockout mice - Agnieszka K. Borowik; Marcus M. Lawrence; Frederick F. Peelor; Katarzyna M. Piekarz; Abby Crosswhite; Arlan Richardson; Benjamin F. Miller; Holly Van Remmen; Jacob L. Brown (GeroScience, 2024)

Understanding different dominance patterns in western Amazonian forests - Laura Matas‐Granados; Frederick C. Draper; Luis Cayuela; Julia G. de Aledo; Gabriel Arellano; Celina Ben Saadi; Timothy R. Baker; Oliver L. Phillips; Eurídice N. Honorio Coronado; Kalle Ruokolainen; Roosevelt García‐Villacorta; Katherine H. Roucoux; et al. (Ecology Letters, 2024)
Dominance of neotropical tree communities by a few species is widely documented, but dominant trees show a variety of distributional patterns still poorly understood. Here, we used 503 forest inventory plots (93,719 individuals ≥2.5 cm diameter, 2609 species) to explore the relationships between local abundance, regional frequency and spatial aggregation of dominant species in four main habitat types in western Amazonia. Although the abundance‐occupancy relationship is positive for the full dataset, we found that among dominant Amazonian tree species, there is a strong negative relationship between local abundance and regional frequency and/or spatial aggregation across habitat types. Our findings suggest an ecological trade‐off whereby dominant species can be locally abundant ( local dominants ) or regionally widespread ( widespread dominants ), but rarely both ( oligarchs ). Given the importance of dominant species as drivers of diversity and ecosystem functioning, unravelling different dominance patterns is a research priority to direct conservation efforts in Amazonian forests.

Driving factors of CO2 emission reduction in the logistics industry: an assessment of the RCEP and SAARC economies - Mukut Sikder; Chao Wang; Frederick Kwame Yeboah; Jacob Wood (Environment, Development and Sustainability, 2022)

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Maximizing Benefits From Punctual Ocean Infrastructure: An Ethical Perspective - Frederick Whoriskey; Michele Barbier; Mackenzie Mazur; Tobias Hahn; Jacob Kritzer; Richard Vallee (Frontiers in Marine Science, 2021)
Ethics are becoming a component of best practices in ocean science and observing systems, with the research community facing a duty to society to maximize the efficient use and benefits that stem from investments in ocean science/monitoring. Sustained ocean observing systems on issues of global importance are coordinated, internationally sanctioned and making the most out of the resources accorded to them and consequently fulfilling their duty to society. However, globally huge investments are made annually in establishing infrastructure for shorter-term, punctual studies that address targeted as opposed to broad science needs. More could be done to maximize the benefits and impacts of these punctual efforts. Given punctual infrastructure’s small and frequently transient nature, connections to enable sharing will probably be done locally, and both potential additional users and owners of the infrastructure will need to be energetic, receptive and flexible. The accommodation of new uses will have to be balanced against any costs of these additional activities, which could pose an ethical dilemma in themselves if they compromise the infrastructure’s ability to meet its original intent. However, such adaptive infrastructures may be the most efficient way to provide the resources needed to identify and monitor emerging or new ocean stressors.

Seeding Dynamics from a Local Seed Mixture on a Bioengineered Riverbank Protection Structure - Magali Weissgerber; Renaud Jaunatre; Fanny Dommanget; Frederick Jacob; Ghislain Huyghe; André Evette (Environmental Management, 2019)

Temporal and Spatial Habitats of Anadromous Brook Charr in the Laval River and its Estuary - R. Allen Curry; Jacob van de Sande; Frederick G. Whoriskey (Environmental Biology of Fishes, 2006)